Impact of the 'public procurement rules 2008' on the implementation of construction projects : a case study on the public works department - Md. Aman Ullah (BRAC University, 2015)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.